2019
DOI: 10.1016/j.celrep.2019.10.002
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous Pain Disrupts Ventral Hippocampal CA1-Infralimbic Cortex Connectivity and Modulates Pain Progression in Rats with Peripheral Inflammation

Abstract: Highlights d Ventral hippocampal CA1-infralimbic cortex (vCA1-IL) connectivity is involved in pain d Persistent spontaneous pain in rats with inflammation disrupts vCA1-IL connectivity d Activating vCA1-IL alleviates spontaneous pain and promotes overall pain recovery d BDNF expression correlates with behavior and activity changes in spontaneous pain

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 49 publications
(39 citation statements)
references
References 76 publications
1
35
0
1
Order By: Relevance
“…Future exploration of other cortical regions that respond to transient nociceptive stimulation will allow testing the contribution of structures other than primary sensorimotor cortices to GBOs measured at both epidural and scalp levels. The last caveat is particularly relevant when considering that GBOs whose magnitude tracks the time-varying fluctuations of the intensity of tonic pain in healthy subjects (Schulz et al, 2015) and in patients with chronic pain (Zhou et al, 2018;May et al, 2019) have been described to originate from the prefrontal cortex and cerebellum, and not from the primary sensorimotor cortices (Schulz et al, 2015;Zhou et al, 2018;Ma et al, 2019;May et al, 2019). This discrepancy might dovetail with the difference of pain types between the above-mentioned studies and the current study, which is also reflected in the different patterns of brain activation observed during chronic pain vs. transient cutaneous pain (Mouraux and Iannetti, 2018, their Fig.…”
Section: Nociceptive-induced Gbos Reflect Spiking Of S1 Interneuronsmentioning
confidence: 99%
“…Future exploration of other cortical regions that respond to transient nociceptive stimulation will allow testing the contribution of structures other than primary sensorimotor cortices to GBOs measured at both epidural and scalp levels. The last caveat is particularly relevant when considering that GBOs whose magnitude tracks the time-varying fluctuations of the intensity of tonic pain in healthy subjects (Schulz et al, 2015) and in patients with chronic pain (Zhou et al, 2018;May et al, 2019) have been described to originate from the prefrontal cortex and cerebellum, and not from the primary sensorimotor cortices (Schulz et al, 2015;Zhou et al, 2018;Ma et al, 2019;May et al, 2019). This discrepancy might dovetail with the difference of pain types between the above-mentioned studies and the current study, which is also reflected in the different patterns of brain activation observed during chronic pain vs. transient cutaneous pain (Mouraux and Iannetti, 2018, their Fig.…”
Section: Nociceptive-induced Gbos Reflect Spiking Of S1 Interneuronsmentioning
confidence: 99%
“…Depression is associated with smaller hippocampal volumes and changes in either the activation or connectivity of neural networks (Etkin et al, 2015;Ma et al, 2019). Depression also increases the level of inflammatory factors in the hippocampus (Fasick et al, 2015), downregulates BDNF (Krishnan and Nestler, 2008), and impairs synaptic plasticity (Otte et al, 2016), all of which contribute to the development and long-term pathophysiology of depression.…”
Section: Introductionmentioning
confidence: 99%
“…It was shown that excitability of infralimbic neurons is significantly suppressed in chronic pain [Chung et al, 2017]. Hippocampal BDNF overexpression accelerates recovery from inflammatory pain and reduces spontaneous pain following the recovery of electrophysiological parame- ters in ventral hippocampal CA1-infralimbic cortex connectivity [Ma et al, 2019]. Along with a decrease in BDNF, we observed an increase in the neurotrophic factor NT-3.…”
Section: Discussionmentioning
confidence: 61%